c-myc oncogene aberration in breast cancer patients assessed by direct double differential PCR - Bednarz, Natalia; Kuberczyk, Maria; Żaczek, Anna; Bielawski, Krzysztof Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
Breast cancer is the most frequent tumour diagnosed in women, especially in well-developed countries. One of the genes of the highest interest in its diagnosis and prognosis is protooncogene c-myc, which plays a role as a transcriptional factor and a key factor in regulation of the cell cycle. Expression of protooncogene c-myc is often impaired in the case of various tumours and its gene amplification is one of its activation mechanisms. In this work we used dddPCR (direct double differential PCR), described in 1999, which has not been applied in research or practice in a broader way before now. The advantages of this technique are: simple and fast sample preparation, reliable results and low cost in comparison to other methods used in molecular biology such as FISH or real-time PCR. Material for investigation was DNA isolated from tumours of 138 patients diagnosed with breast cancer. Clinical characterizations of particular tumours were different regarding tumour status, node status, presence of oestrogen and progesterone receptors, histological type of tumour and its histopathological grading. We found amplification of c-myc protooncogene in 20 of 138 samples (14.5%); however, there was no statistically significant correlation between c-myc amplification and other clinical features. A reverse correlation between AGCN (average gene copy number) value and tumour status was found.